Jambi Batik Industry as a Source of Income to Improve Community Welfare - Simarmata, Jonner; Adriani, Evi (Greenation International Journal of Tourism and Management, 2025)
This study aims to analyze the potential of the Jambi Batik Industry as a source of improving community welfare. This study employed a literature review method through analysis of various relevant written sources, such as books, scientific articles, government reports, and other official documents. The results indicate that the Jambi Batik Industry has significant economic potential to improve community welfare, through job creation, increased income, and strengthening creative economic businesses based on local culture. However, this industry faces various obstacles, including low competitiveness, limited local design innovation, narrow market orientation, and suboptimal institutional support. This study confirms that optimizing the Jambi Batik Industry's contribution to improving community welfare requires a comprehensive development strategy, encompassing strengthening human resource capacity, innovation, market expansion, government policy support, and product diversification.